Implementasi Kurikulum yang Memberdayakan Konteks? - Arinta Kintan Larasati; Masduki Asbari; Putri Hafizhah Pinandita; Adhinta Darusancia Anggaini Putri (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to find out how the curriculum is implemented in the archipelago. As has been said, Indonesia has many islands and regions, so the implementation of the curriculum in each region is different. The need for education in developing an applicable curriculum, in order to improve the quality of human resources in the future. This study report uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to oral narratives from the YouTube channel Teacher Learning Stories entitled "Curriculum Implementation that Empowers Context by Najelaa Shihab". The results of this study explain that in implementing the curriculum it is necessary to hold educators' meetings so that they can exchange ideas about the state of education in Indonesia. Basically, implementing an appropriate curriculum requires the role of educators who are able to understand students. The curriculum has a very important meaning and is always related to education. If the curriculum can run well and correctly, then the learning process will run well too.